Bio-Guided Fractionation and Molecular Networking Reveal Fatty Acids to Be Principal Anti-Parasitic Compounds in Nordic Seaweeds - Bonde, Charlotte Smith; Bornancin, Louis; Lu, Yi; Simonsen, Henrik Toft; Martínez-Valladares, María; Peña-Espinoza, Miguel; Mejer, Helena; Williams, Andrew R.; Thamsborg, Stig Milan (Frontiers in Pharmacology, 2021)
Widespread use of antimicrobial drugs has led to high levels of drug-resistant pathogen populations, necessitating a need for novel sources of anti-bacterial and anti-parasitic compounds. Macroalgae (seaweed) are potentially a rich source of bioactive compounds, and several species have traditionally been used as vermifuges. Here, we investigated the anti-parasitic properties of four common cold-water Nordic seaweeds; Palmaria palmata, Laminaria digitata, Saccharina latissima and Ascophyllum nodosum. Screening of organic extracts against helminths of swine (Ascaris suum) and sheep (Teladorsagia circumcincta) revealed that S. latissima and L. digitata had particularly high biological activity. A combination of molecular networking and bio-guided fractionation led to the isolation of six compounds from extracts of these two species identified in both fermented and non-fermented samples. The six isolated compounds were identified as five fatty acids and one monoglyceride: Stearidonic acid (1), Eicosapentaenoic acid (2), Alpha-Linolenic acid (3), Docosahexaenoic acid (4), Arachidonic acid (5), and Monoacylglycerol (MG(20:5/0:0/0:0)) (6). Individual compounds showed only modest activity against A. suum, but a clear synergistic effect was apparent when selected compounds were tested in combination. Collectively, our data reveal that fatty acids have a previously unappreciated potential role as natural anti-parasitic compounds, which suggests that seaweed products may represent a viable option for control of intestinal helminth infections.